Ginger extract inhibits human telomerase reverse transcriptase and c-Myc expression in A549 lung cancer cells. - Wirote Tuntiwechapikul (2018)
The rhizome of ginger (Zingiber officinale Roscoe) has been reputed to have many curative properties in traditional medicine, and recent publications have also shown that many agents in ginger possess anticancer properties. Here we show that the ethyl acetate fraction of ginger extract can inhibit the expression of the two prominent molecular targets of cancer, the human telomerase reverse transcriptase (hTERT) and c-Myc, in A549 lung cancer cells in a time- and concentration-dependent manner. The treated cells exhibited diminished telomerase activity because of reduced protein production rather than direct inhibition of telomerase. The reduction of hTERT expression coincided with the reduction of c-Myc expression, which is one of the hTERT transcription factors; thus, the reduction in hTERT expression might be due in part to the decrease of c-Myc. As both telomerase inhibition and Myc inhibition are cancer-specific targets for cancer therapy, ginger extract might prove to be beneficial as a complementary agent in cancer prevention and maintenance therapy.